P2X1‐regulated IL‐22 secretion by innate lymphoid cells is required for efficient liver regeneration. Issue 6 (17th March 2016) - Kudira, Ramesh; Malinka, Thomas; Kohler, Andreas; Dosch, Michel; de Agüero, Mercedes Gomez; Melin, Nicolas; Haegele, Stefanie; Starlinger, Patrick; Maharjan, Niran; Saxena, Smita; Keogh, Adrian; Stroka, Deborah; et al.
Abstract : Paracrine signalling mediated by cytokine secretion is essential for liver regeneration after hepatic resection, yet the mechanisms of cellular crosstalk between immune and parenchymal cells are still elusive. Interleukin‐22 (IL‐22) is released by immune cells and mediates strong hepatoprotective functions. However, it remains unclear whether IL‐22 is critical for the crosstalk between liver lymphocytes and parenchymal cells during liver regeneration after partial hepatectomy (PH). Here, we found that plasma levels of IL‐22 and its upstream cytokine, IL‐23, are highly elevated in patients after major liver resection. In a mouse model of PH, deletion of IL‐22 was associated with significantly delayed hepatocellular proliferation and an increase of hepatocellular injury and endoplasmic reticulum stress. Using Rag1 −/− and Rag2 −/− γc −/ − mice, we show that the main producers of IL‐22 post‐PH are conventional natural killer cells and innate lymphoid cells type 1. Extracellular adenosine triphosphate (ATP), a potent danger molecule, is elevated in patients immediately after major liver resection. Antagonism of the P2‐type nucleotide receptors, P2X1 and P2Y6, significantly decreased IL‐22 secretion ex vivo . In vivo, specific inhibition of P2X1 was associated with decreased IL‐22 secretion, elevated liver injury, and impaired liver regeneration. Conclusion: This study shows that innate immune cell‐derived IL‐22 is required for efficient liver regeneration and that secretion of IL‐22 in the regenerating liver is modulated by the ATP receptor, P2X1. (Hepatology 2016;63:2004‐2017)